Mutant Wars2 gene in spontaneously hypertensive rats impairs brown adipose tissue function and predisposes to visceral obesity - Pravenec, M; Zídek, V; Landa, V; Mlejnek, P; Šilhavý, J; Šimáková, M; Trnovská, J; Škop, V; Marková, I; Malínská, H; Hüttl, M; Kazdová, L; et al. (Physiological research, 2017)
Brown adipose tissue (BAT) plays an important role in lipid and glucose metabolism in rodents and possibly also in humans. Identification of genes responsible for BAT function would shed light on underlying pathophysiological mechanisms of metabolic disturbances. Recent linkage analysis in the BXH/HXB recombinant inbred (RI) strains, derived from Brown Norway (BN) and spontaneously hypertensive rats (SHR), identified two closely linked quantitative trait loci (QTL) associated with glucose oxidation and glucose incorporation into BAT lipids in the vicinity of Wars2 (tryptophanyl tRNA synthetase 2 (mitochondrial)) gene on chromosome 2. The SHR harbors L53F WARS2 protein variant that was associated with reduced angiogenesis and Wars2 thus represents a prominent positional candidate gene. In the current study, we validated this candidate as a quantitative trait gene (QTG) using transgenic rescue experiment. SHR-Wars2 transgenic rats with wild type Wars2 gene when compared to SHR, showed more efficient mitochondrial proteosynthesis and increased mitochondrial respiration, which was associated with increased glucose oxidation and incorporation into BAT lipids, and with reduced weight of visceral fat. Correlation analyses in RI strains showed that increased activity of BAT was associated with amelioration of insulin resistance in muscle and white adipose tissue. In summary, these results demonstrate important role of Wars2 gene in regulating BAT function and consequently lipid and glucose metabolism.
Keywords: mutace; Animals; Adipose Tissue, Brown; hnědá tuková tkáň; Phenotype; tryptofan-tRNA-ligasa; Mitochondria; Obesity; energetický metabolismus; Lipid Metabolism; Intra-Abdominal Fat; Energy Metabolism; Mutation; genetická predispozice k nemoci; kultivované buňky; Genetic Predisposition to Disease; Rats, Inbred SHR; metabolismus lipidů; mitochondrie; Cells, Cultured; genetické asociační studie; obezita; Male; glukosa; Glucose; nitrobřišní tuk; potkani inbrední SHR; Quantitative Trait Loci; fenotyp; zvířata; mužské pohlaví; lokus kvantitativního znaku; Tryptophan-tRNA Ligase; Genetic Association Studies